Chance - Iversen, Margaret (Cambridge, MA : Whitechapel Gallery, the MIT Gallery, 2010)
Artists surveyed include: Vito Acconci, Bas Jan Ader, Francis Alÿs, William Anastasi, John Baldessari, Walead Beshty, Mark Boyle, George Brecht, Marcel Broodthaers, John Cage, Sophie Calle, Tacita Dean, Stan Douglas, Marcel Duchamp, Brian Eno, Fischli & Weiss, Ceal Floyer, Huang Yong Ping, Douglas Huebler, Allan Kaprow, Alison Knowles, Jiri Kovanda, Jorge Macchi, Christian Marclay, Cildo Meireles, Robert Morris, Bruce Nauman, Yoko Ono, Gabriel Orozco, Cornelia Parker, Robert Rauschenberg, Gerhard Richter, Daniel Spoerri, Keith Tyson, Jennifer West, Ceryth Wyn Evans, La Monte Young. Writers include: Paul Auster, Jacquelynn Baas, Georges Bataille, Daniel Birnbaum, Claire Bishop, Guy Brett, Benjamin H.D. Buchloh, Stanley Cavell, Lynne Cooke, Fei Dawei, Gilles Deleuze, Anna Dezeuze, Russell Ferguson, Branden W. Joseph, Siegfried Kracauer, Jacques Lacan, Sarat Maharaj, John Miller, Alexandra Munroe, Gabriel Pérez Barreiro, Jasia Reichardt, Julia Robinson, Sarah Valdez, Katharina Vossenkuhl.-
boek
Keywords: Chance in art